Production of functional yogurt drink, appel and orange juice using nano-encapsulated L. Brevis whitin sodium algınate-based biopolymers - Mohaisen, Mohammed Jawad (My University, 2019)
This study aims to improve the functional properties of ayran, apple and orange juice, which were produced by the addition of free and encapsulated probiotics. Thus, probiotic L. brevis E25 bacterial cells were encapsulated in sodium alginate using the electrospinning method. In this study, fourier-transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), XRD, and Nuclear Magnetic Resonance (NMR) techniques were used to characterize the L. brevis encapsulated with nanofiber. The free and nano-encapsulated probiotic bacteria were inoculated into ayran, apple and orange juice, where bacterial viability, pH, Brix, and color were assessed every three days for the ayran and each week for the apple and orange juice for a six-week period. The encapsulated probiotic microorganisms showed an important survival ratio in the three products comparing to the free probiotic bacteria, where the pH and the Brix showed no decreasing leading to conclude that the nano-encapsulation of probiotic L. brevis cell using the electrospinning method lead to functional yet more stable food and have the potential of increased benefits.

Bu çalışmanın amacı, serbest ve kapsüllenmiş probiyotiklerin eklenmesiyle üretilen yoğurtlu içecek, elma ve portakal suyunun fonksiyonel özelliklerini iyileştirmekti.Bu amaçla probiyotik L. brevis E25 bakteri hücreleri, elektrospinning yöntemi ile sodyum aljinatta kapsüllenmiştir. Bu çalışmada, fourier-transform kızılötesi (FT-IR) spektroskopisi, taramalı elektron mikroskobu (SEM), XRD ve Nükleer Manyetik Rezonans (NMR) teknikleri, nanofiber ile kaplanmış L. Brevis'i karakterize etmek için kullanılmıştır. Serbest ve nano kapsüllenmiş probiyotik bakteriler, ayran, elma ve portakal suyuna inoküle edilmiştir. Altı hafta boyunca ayran için her üç günde bir elma ve portakal suyu için her hafta örnek alınarak bakteri canlılığı, pH, Brix ve renk ölçümleri alınmıştır. Enkapsüle probiyotik organizmalar her üç üründe, serbest probiyotik bakterilere kıyasla önemli oranda hayatta kalma oranı göstermiştir. Bu sonuç ile pH ve Brix değerlerinin azalma göstermemesi elektrospin metoduyla probiyotik L.brevis’in nanoenkapsülasyonunun fonksiyonel ürünün stabilitesini sağladığı ve ürünün potansiyel faydalarını arttırdığı sonucuna ulaşılmıştır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Nanoencapsulation; L. brevis; Electrospinning; Fruit juice.; Probiotic